Effect of calcium ions on scheelite flotation using mixed collectors. Issue 1 (2nd January 2019) - Dong, Liuyang; Zhu, Hailing; Jiao, Fen; Qin, Wenqing; Jia, Wenhao
ABSTRACT: The flotation results show that Ca 2+ significantly reduces the flotation recovery of scheelite using single dodecylamine (DDA) or single sodium oleate (NaOL), whereas Ca 2+ hardly affects scheelite recovery using mixed collectors DDA/NaOL. Zeta potential measurements and solution chemistry confirm that the zeta potential of scheelite shows a significant positive shift after conditioning of Ca 2+, which hinders the adsorption of same positively charged DDA on the mineral surface. Simultaneously, the addition of Ca 2+ consumes single NaOL and generates Ca(OL)2 . As for DDA/NaOL, the predominant components are RNH3 + and RCOO − at pH 7; they form new highly active complexes through electrostatic attraction, reducing adverse effect of Ca 2+ . Fourier transform infrared spectroscopy measurements and adsorption measurements further confirm that the pre-adsorption of Ca 2+ does not interfere with the adsorption of mixed collectors.